Moral Education in Early Childhood: The Existence of TPA Darul Amin in Urban Communities - Mazrur Mazrur; Surawan Surawan; M. Ali Sibram Malisi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Moral education is not only carried out through formal education, but can also be carried out through non-formal channels, one of which is through TPA (Al-Qur'an Education Park). This research wants to explore the methods of forming children's attitudes and the efforts made by teachers/ustadz in forming children's attitudes. This research was compiled using a descriptive qualitative approach and is located at TPA Darul Amin Palangka Raya. Collecting data through observation, interviews, and documentation. The research was carried out from October to November 2022, by being directly involved in TPA learning 3 times a week. Data validation using triangulation of data sources was analyzed through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the methods used include habituation methods, exemplary methods, story methods and singing methods, and the ustadz's efforts in shaping the child's attitude are greeting, getting used to praying after and before learning, using learning methods, giving advice and examples, supervising and getting used to speaking well, providing motivation and getting used to discipline.